Foreword - Batlle, A; Rossetti, M V (Cellular and Molecular Biology, 2009)
To begin with, we wish to thank again Professor Dr. Raymond Wegmann "The Founding President” and Professor Dr. Jean-Michel Maixent, "The President”, Editors-in-Chief of Cellular and Molecular BiologyTM for their generous invitation to become Guest- Editor and Co-Guest Editor of this special theme issue on "Porphyrias and associated pathologies. Biochemistry and Molecular Biology”, which has been published in two Volumes, Part I, appeared in February 16 th, 2009 and now, Part II, scheduled for July 1 st 2009.